THE COMPARISON OF COMPUTERIZED AND NON COMPUTERIZED INFORMATION SYSTEM OF MANAGEMENT TOWARD THE PERFORMANCE OF PHARMACY X AND PHARMACY IN PURWOKERTO - Lingga Ikaditya; Hari Kusnanto; Tri Murti Andayani (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The use of management information systems applications (SIM) based on computers is still very rare in health facilities such as pharmacies. Ussually, the drug management is done manually so the accuracy of drug management is not good. Based on that problem, research on the application of management information system is needed to see the performance of pharmacies with SIM based on computerize and non-computeize. This study aimed to know the performance of pharmacies in terms of the efficiency of the management of the drug, human resources efficiency and the quickness service of SIM application with computerized and non-computerized. The research metthod was descriptive analytic design by using case studies at the pharmacy X with computerized SIM and Pharmacy Y with non computerized SIM. The data analysis for the management of drug used efficiency of medication management indicators, human resource efficiency used workload analysis, and the speed of measurement time service used dispensing time. The result illustrated that the efficiency of the management of computerized pharmacy medication was better than the non computerized pharmacies. In terms of human resources efficiency levels, as seen from the composition of the human resources required indicated that non computerized pharmacies needed more human resources than computerized pharmacies, as well as the rate speed of service to patients showed that computerized pharmacies was quicker in the service. Keywords: Pharmacy, SIM computerized, SIM non computerized